2009
DOI: 10.1152/japplphysiol.00564.2009
|View full text |Cite
|
Sign up to set email alerts
|

The phenotype and potential origin of nestin+cardiac myocyte-like cells following infarction

Abstract: Nestin+ cardiac myocyte-like cells were detected in the peri-infarct/infarct region of the ischemically damaged heart. The present study was undertaken to elucidate the phenotype and potential origin of nestin+ cardiac myocyte-like cells and identify stimuli implicated in their appearance. In the infarcted human and rat heart, nestin+ cardiac myocyte-like cells were morphologically and structurally immature, exhibited a desmin-immunoreactive striated phenotype, expressed the beta(1)-adrenergic receptor, and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 28 publications
4
21
0
Order By: Relevance
“…Following ischemic damage, nestin ϩ cells migrated to the infarct region, and work from our laboratory and others have reported their involvement in neural remodeling and de novo blood vessel formation as a cellular substrate of angiogenesis (6,20,21,26,50,53). Additional evidence supports the premise that a subpopulation of cardiac resident nestin ϩ cells may directly contribute to myocardial regeneration (5,26,53). Nestin expression was not limited to neural progenitor/stem cells since the intermediate filament protein was also detected in endothelial cells of newly formed blood vessels in the infarct region and a subpopulation of scarderived myofibroblasts (4,6,21).…”
supporting
confidence: 61%
See 3 more Smart Citations
“…Following ischemic damage, nestin ϩ cells migrated to the infarct region, and work from our laboratory and others have reported their involvement in neural remodeling and de novo blood vessel formation as a cellular substrate of angiogenesis (6,20,21,26,50,53). Additional evidence supports the premise that a subpopulation of cardiac resident nestin ϩ cells may directly contribute to myocardial regeneration (5,26,53). Nestin expression was not limited to neural progenitor/stem cells since the intermediate filament protein was also detected in endothelial cells of newly formed blood vessels in the infarct region and a subpopulation of scarderived myofibroblasts (4,6,21).…”
supporting
confidence: 61%
“…The latter cells were partially elongated and appeared to be in a primordial state of differentiation possibly to a cardiac myocyte-like cell. These data and the findings by Tomita and colleagues (53) suggested that a subpopulation of rat cardiac resident nestin ϩ cells expressing GATA4/NKX2.5 may represent a novel cardiac progenitor stem cell pool implicated in myocardial regeneration during reparative fibrosis (5). The study by Tamura and colleagues (50) have in part substantiated the aforementioned premise as neural crest-derived stem cells [e.g., nestin ϩ , form spheres in the presence of EGF/bFGF, c-kit…”
Section: Nestin ϩ Cardiac Myocyte-like Cells and Reparative Fibrosismentioning
confidence: 60%
See 2 more Smart Citations
“…Despite the plethora of data supporting the premise that nestin expression identified a stem cell phenotype, recent studies have detected the intermediate filament protein in numerous non-stem cell populations during physiological growth and pathological remodeling. Nestin was highly expressed in developing skeletal myofibers and downregulated following maturation, upregulated in endothelial cells during reparative angiogenesis, and induced in mesangial cells following injury and in scar myofibroblasts and cardiac myocyte-like cells bordering the peri-infarct/infarct region of the ischemically damaged rodent and human heart (1,3,4,7,9,11,24,25,31,32). However, in contrast to neural progenitor/stem cells, expression of the intermediate filament protein in skeletal myofibers and endothelial cells was driven by the first intron of the nestin gene (1,42,43).…”
mentioning
confidence: 99%